2003
DOI: 10.1101/gad.1076103
|View full text |Cite
|
Sign up to set email alerts
|

Transient activation of β-catenin signaling in cutaneous keratinocytes is sufficient to trigger the active growth phase of the hair cycle in mice

Abstract: Wnts have key roles in many developmental processes, including hair follicle growth and differentiation. Stabilization of ␤-catenin is essential in the canonical Wnt signaling pathway. We developed transgenic mice expressing a regulated form of ␤-catenin in the skin. Chronic activation of ␤-catenin in resting (telogen) hair follicles resulted in changes consistent with induction of an exaggerated, aberrant growth phase (anagen). Transient activation of ␤-catenin produced a normal anagen. Our data lend strong s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
193
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(209 citation statements)
references
References 20 publications
13
193
0
3
Order By: Relevance
“…Since mice undergo two sequential waves of hair growth before entering a prolonged telogen phase at 6 weeks of age (Muller-Rover et al, 2001;Stenn and Paus, 2001), we began the 4OHT treatment at 6 weeks of age to ensure that the follicles would be in telogen for at least 3 weeks after initiating the 4OHT treatment. No hair regrowth was observed in the skin of transgenic mice treated with ethanol alone or wild-type mice treated with 4OHT (data not shown), as previously reported (Van Mater et al, 2003;Lo Celso et al, 2004). In contrast, drastic changes were detected in the transgenic mice treated with 4OHT ( Figure 2).…”
Section: Induction Of Epidermal Hyperplasia By Akt Signaling Activatisupporting
confidence: 86%
See 1 more Smart Citation
“…Since mice undergo two sequential waves of hair growth before entering a prolonged telogen phase at 6 weeks of age (Muller-Rover et al, 2001;Stenn and Paus, 2001), we began the 4OHT treatment at 6 weeks of age to ensure that the follicles would be in telogen for at least 3 weeks after initiating the 4OHT treatment. No hair regrowth was observed in the skin of transgenic mice treated with ethanol alone or wild-type mice treated with 4OHT (data not shown), as previously reported (Van Mater et al, 2003;Lo Celso et al, 2004). In contrast, drastic changes were detected in the transgenic mice treated with 4OHT ( Figure 2).…”
Section: Induction Of Epidermal Hyperplasia By Akt Signaling Activatisupporting
confidence: 86%
“…The activation of Wnt/b-catenin signaling brings about similar phenotypes in adult epidermis (Gat et al, 1998;Van Mater et al, 2003;Lo Celso et al, 2004). The mice expressing stabilized b-catenin or b-cateninMer fusion protein show epidermal hyperplasia, hair follicle tumor-like outgrowth and precocious transition from telogen to anagen phase via activation of stem cells.…”
Section: Proliferation Of Keratinocyte Progenitors By Akt Signalingmentioning
confidence: 99%
“…The demonstration that HR function in progenitor keratinocytes is sufficient for hair follicle regeneration led us to investigate whether HR regulates Wnt signaling, because activation of this pathway in these cells has been directly implicated in hair follicle regeneration (31)(32)(33)(34)(35). We examined expression of a Wnt-responsive gene, Axin2 (36)(37)(38), and found that Axin2 expression is not detected in Hr Ϫ/Ϫ hair follicles at anagen initiation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conditional deletion of b-catenin in adult mouse epidermis leads to HF degeneration and cyst formation, demonstrating the essential function of b-catenin in maintaining the identity of adult HF SCs (Lowry et al 2005). Increased levels of b-catenin in adult HF SCs results in the shortening of telogen and the acceleration of telogen to anagen transition (Van Mater et al 2003;Lo Celso et al 2004;Lowry et al 2005), with a concomitant increase in bulge SC proliferation (Lowry et al 2005). Transcriptional profiling of bulge SCs during telogen and anagen, as well as following b-catenin gain-of-function expression, identified a set of genes modulated by Wnt/b-catenin signaling and associated with anagen reentry.…”
Section: Hf Morphogenesis and Cyclingmentioning
confidence: 99%